Pengaruh Model Pembelajaran Terhadap Kompetensi SDM Vokasional di Era Industri 4.0: Studi Literatur - Wardoyo, Siswo; Marsanda, Elisa; Wulansari, Tari; Anjani, Triska Adelia; Anzhari, Hafizh; Abdillah, Muhammad Zaqqi (Universitas Lampung, 2024)
The Influence of Learning Models: In the era of the Industrial Revolution 4.0, Indonesian education faces a major challenge to improve the quality of human resources that are able to adapt to technological advances and industrial needs. The purpose of this study is to determine how learning models impact the capabilities of vocational human resources in the digital era. The method used is to conduct literature research by collecting information from various sources, such as books and journal articles related to the subject. The results of the study indicate that new learning models such as direct instruction, computational thinking, and project-based learning can improve students' soft skills and vocational skills. This is very important to compete in the job market. In addition, collaboration between teachers, students, and education personnel is key to creating an interesting learning experience that is relevant to industrial developments. This study concludes that vocational education needs to adopt a more innovative and integrated approach, as well as adjust the curriculum to meet the demands of industry 4.0, so that graduates can become individuals who are ready to work, adaptive, and have the skills needed. Kata kunci: Industri 4.0, Model Pembelajaran, SDM